Knowledge, Attitude and Practice of Lifestyle Modifications Among Hypertensive Patients Visiting A Tertiary Care Hospital in Central India - Amborkar, Deepti; Kasulkar, Arti; Gupta, Madhur (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Globally, hypertension is a major problem. The cornerstone of the strategy for preventing hypertension is making appropriate lifestyle modifications. The present study was carried out to assess knowledge, attitude and practice of lifestyle modifications among hypertensive patients. Methods: This cross-sectional questionnaire-based study carried out among 343 hypertensive patients visiting a tertiary care hospital. Results: We observed that although majority of hypertensive had good knowledge and attitude about lifestyle changes in hypertension, least were adherent to those. Conclusion: The treatment of hypertension is greatly aided by preventive medication. In order to lower the prevalence of hypertension in a nation, assessments of knowledge, attitudes, and practices regarding lifestyle change are fundamentally necessary. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 140-146